2018
DOI: 10.1155/2018/9189062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Late Evening Snack on Cirrhotic Patients: A Systematic Review and Meta-Analysis

Abstract: Background Energetic effects of late evening snack (LES) on cirrhotic patients were reported recently, but there was no quantitative analysis. In this meta-analysis, we reviewed and quantified the effects of LES on energy metabolism and substrate oxidation in the patients with cirrhosis, which will be of benefit for liver cirrhosis nutritional therapy. Methods A systematic search was conducted in PubMed, Embase, Web of Science, Elsevier, China National Knowledge Infrastructure, and Wanfang Database for relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
(34 reference statements)
0
14
0
1
Order By: Relevance
“…This study is the first to determine the association between LES therapy and improved survival in patients with cirrhosis. A LES has been shown to improve the nutritional status, liver function reserves, and sarcopenia in patients with cirrhosis [8][9][10], each of which raises the potential to improve the survival of these patients; however, little is known about the survival benefit of LES thus far. The novelty of our study is that LES-treated patients demonstrated a significantly higher overall survival than PS-matched patients who did not receive LES therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first to determine the association between LES therapy and improved survival in patients with cirrhosis. A LES has been shown to improve the nutritional status, liver function reserves, and sarcopenia in patients with cirrhosis [8][9][10], each of which raises the potential to improve the survival of these patients; however, little is known about the survival benefit of LES thus far. The novelty of our study is that LES-treated patients demonstrated a significantly higher overall survival than PS-matched patients who did not receive LES therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the influence of meal patterns on energy metabolism have shown that a late evening snack (LES), which is defined as an oral intake of a branched-chain amino acids (BCAA)-enriched nutrient before bedtime, and more frequent oral intake improve the catabolic state of patients with cirrhosis [8]. A LES has been reported to improve not only the nutritional status but also clinical outcomes, including ascites, HE, and health-related quality of life in patients with cirrhosis [8][9][10]. Therefore, clinical practice guidelines recommend that patients with cirrhosis receive LES therapy to improve their clinical outcomes [1,7,11].…”
Section: Introductionmentioning
confidence: 99%
“…An optimal supply of macro and micronutrients is the mainstay of nutritional therapy in CLD patients. A recent meta-analysis demonstrated the impact of a late evening snack on energy metabolism in LC patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, longer postprandial periods are desired in cirrhosis to improve nutrition status, and the consumption of several small meals is a step toward this direction. In addition, based on a recent systematic review, a late‐evening snack can be used as a means to improve malnutrition among cirrhotic patients and ameliorate morning starving state, and this is why some CPGs suggested the consumption of a late‐night snack.…”
Section: Discussionmentioning
confidence: 99%